Evidence-Based Cerebral Vasospasm Surveillance - Heather Kistka; Michael C. Dewan; J. Mocco (Neurology Research International)
Subarachnoid hemorrhage related to aneurysmal rupture (aSAH) carries significant morbidity and mortality, and its treatment is focused on preventing secondary injury. The most common—and devastating—complication is delayed cerebral ischemia resulting from vasospasm. In this paper, the authors review the various surveillance technologies available to detect cerebral vasospasm in the days following aSAH. First, evidence related to the most common modalities, including transcranial doppler ultrasonography and computed tomography, are reviewed. Continuous electroencephalography and older instruments such as positron emission tomography, xenon-enhanced CT, and single-photon emission computed tomography are also discussed. Invasive strategies including brain tissue oxygen monitoring, microdialysis, thermal diffusion, and jugular bulb oximetry are examined. Lastly, near-infrared spectroscopy, a recent addition to the field, is briefly reviewed. Each surveillance tool carries its own set of advantages and limitations, and the concomitant use of multiple modalities serves to improve diagnostic sensitivity and specificity.